2015
DOI: 10.1016/j.nicl.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of the early detection of synaptic dysfunction in Mild Cognitive Impairment using Magnetoencephalography-derived functional connectivity

Abstract: Synaptic disruption is an early pathological sign of the neurodegeneration of Dementia of the Alzheimer's type (DAT). The changes in network synchronization are evident in patients with Mild Cognitive Impairment (MCI) at the group level, but there are very few Magnetoencephalography (MEG) studies regarding discrimination at the individual level. In an international multicenter study, we used MEG and functional connectivity metrics to discriminate MCI from normal aging at the individual person level. A labeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 31 publications
3
71
0
Order By: Relevance
“…85 Additionally, resting-state MEG has shown network hypersynchronisation across multiple frequency bands in frontoparietal and interhemispheric networks in patients with amnestic mild cognitive impairment. 86 …”
Section: Cognition and Epileptiform Activitymentioning
confidence: 99%
“…85 Additionally, resting-state MEG has shown network hypersynchronisation across multiple frequency bands in frontoparietal and interhemispheric networks in patients with amnestic mild cognitive impairment. 86 …”
Section: Cognition and Epileptiform Activitymentioning
confidence: 99%
“…Pathological aging is characterized by early synaptic disruption and synaptic loss that lead to white-matter abnormalities, anatomofunctional connectivity deficits and progressive cognitive decline [29, 57-60]. This is known to be related to the magnitude and spatial distribution of intracellular aggregates of tau protein filaments (neurofibrillary tangles) and the extracellular deposition of Aβ peptides (amyloid plaques) [29, 57].…”
Section: Oscillation-based Connectivitymentioning
confidence: 99%
“…Thus, recent studies have looked at neuronal network organization in cognitively normal elderly subjects and in patients with AD, and its association with disease biomarkers. In addition to abnormalities in alpha source oscillatory activity, disruption in functional connectivity in the alpha band is reported in biomarker-positive elderly subjects who progress to AD and in patients who have developed the disease [57, 60-62]. Rossini et al [61] reported the changes of cortical connectivity and LORETA sources of EEG rhythms between the baseline (i.e., at the time of MCI diagnosis) and follow-up (approx.…”
Section: Oscillation-based Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…of the disease [4,5]. For example, in individuals with mild cognitive impairment (MCI), reductions in sensor-space N400 (see below) or P600 word repetition effects are associated with greater likelihood of subsequent transition to AD dementia [6].…”
Section: W Penny Et Al / Dynamic Causal Modeling Of Preclinical Eegmentioning
confidence: 99%